Factor Influencing Online Learning for Higher Education in Pandemic Covid-19 and Impact to Word of Mouth - Achmadi, Hendra; Bernarto, Innocentius; Patria, Danet; Hutabarat, Moses; Pramono, Rudy (Budapest International Research and Critics University, 2021)
With the Covid-19 pandemic in early March 2020 to 2021, it has changed the learning patterns of students in high school and students at universities or in higher education. This study was conducted to examine the factors that influence online learning from students at higher education universities, besides that in this study also to test whether the self-efficacy factor affects students at the university. This study uses a quantitative method, by taking primary data 112 primary data from universities, and distributed using google form. After the data is collected, using the confirmatory Composite Analysis method and also using PLS-SEM, to test whether there is a high correlation between factors or not. After knowing the components that affect online learning, the results show that Self Efficacy meets the criteria for confirmatory composite analysis testing, so that Self Efficacy becomes a reliable and valid dimension in Online Learning, and ranks first with an R2 of 0.821 which has an effect on Online Learning. In this study, online learning also has a major effect on WOM, which is 0.816 and can also be seen from R2 of WOM, which is 0.665 which is included in Moderate Predictive Accuracy, so it can be concluded that Online Learning has a strong influence on WOM of students who are studying during a pandemic, so that very influential on the marketing of the college.